El diseñador gráfico dentro del esquema de una oficina de comunicaciones: el caso de la fundación universitaria san Martín - Garzón Caro, Brayan Andres (Universidad Antonio Nariño, 2021)
Labor practices are a mechanism which is given to a student who is close to completing his university studies in order to grant him the relevant work experience and learning to have the basic tools to face the new work environment that He hopes and this will give the student a perspective of what a work environment will be like and helps the practitioner in his resume to have minimum requirements that are essential to be able to be part of some work, satisfaction and stimulus are also offered. I encourage students to be part of real projects where the pieces will be directed to different people and thus be able to see their work reflected not only for a teacher but also for a community of people, I think that is one of the largest experiences that can be achieved in this case as a graphic design practitioner, as well as being an enrichment exercise Labor and experience is a fundamental requirement in order to complete the student cycle in which it is located.